Phylogenetic and Functional Analysis of Bacterial Strains Isolated From Glycyrrhiza Glabra L. Roots - Mirzaalievna, Kuralova Ra’ni (American Journal of Biology and Natural Sciences, 2025)
Glycyrrhiza glabra L., commonly known as licorice, is a medicinal plant with significant therapeutic properties. This study aimed to isolate and characterize bacterial strains from the roots of Glycyrrhiza glabra L. using 16S rRNA gene sequencing. The isolated strains were identified as Bacillus licheniformis, Bacillus subtilis, and Bacillus halotolerans. Phylogenetic analysis revealed close relationships with known Bacillus species, indicating potential roles in promoting plant growth, enhancing stress tolerance, and protecting against pathogens. The findings suggest that these bacterial strains could be utilized in agricultural practices to improve plant health and productivity.